2022
DOI: 10.1038/s41419-022-05264-z
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptotic MSCs protect mice against sepsis via promoting macrophage efferocytosis

Abstract: The therapeutic effect of mesenchymal stem cells (MSCs) on sepsis has been well-known. However, a comprehensive understanding of the relationship between MSCs and macrophages remains elusive. Superparamagnetic iron oxide (SPIO) is one of the most commonly used tracers for MSCs. Our previous study has shown that SPIO enhanced the therapeutic effect of MSCs in a macrophage-dependent manner. However, the fate of SPIO-labeled MSCs (MSCSPIO) after infusion remains unknown and the direct interaction between MSCSPIO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…The primary organ for storing iron and metabolizing lipids is the liver. When the liver is impaired, the levels of iron and lipid ROS are significantly elevated ( 45 ). Patients with NAFLD often have increased serum ferritin levels, which are linked to intrahepatic iron accumulation;, iron levels are markedly elevated in the liver when the liver is dysfunctional.…”
Section: Ferroptosis and Nafld/nashmentioning
confidence: 99%
“…The primary organ for storing iron and metabolizing lipids is the liver. When the liver is impaired, the levels of iron and lipid ROS are significantly elevated ( 45 ). Patients with NAFLD often have increased serum ferritin levels, which are linked to intrahepatic iron accumulation;, iron levels are markedly elevated in the liver when the liver is dysfunctional.…”
Section: Ferroptosis and Nafld/nashmentioning
confidence: 99%
“…It is noteworthy that the ability to contribute to the generation of pro-regenerative macrophages may be further increased in MSCs by exposing them to molecules like LPS prior to extracellular vesicle harvesting and administration (Ti et al, 2015). More recently, the use of apoptotic MSCs to mitigate sepsis by promotion of M2 polarization in macrophages has been demonstrated (Pan et al, 2022), which suggests that even allogeneic MSCs induced to become apoptotic could be used to treat conditions that could be improved by increasing the number of M2 macrophages. Acute conditions that affect the brain, in which neuroinflammation greatly contributes to a negative outcome (da Silva Meirelles et al, 2017;Regner et al, 2017), represent a scenario in which these strategies may be particularly useful.…”
Section: Figurementioning
confidence: 99%
“…Apoptosis was also shown to be required for DPSCs to have immunosuppressive functions in an allergic airway inflammation model [ 139 ]. A recent study showed that ferroptosis in MSCs induced by superparamagnetic iron oxide promoted efferocytosis by macrophages and thus enhanced the protective effect on septic mice, while these benefits were impaired after MSCs were treated with inhibitors of ferroptosis [ 140 ]. Whether and how the other fates of MSCs, such as pyroptosis and necroptosis, affect the immunosuppressive functions of MSCs remain to be explored.…”
Section: Introductionmentioning
confidence: 99%